1831 Ind. Rev. Stat. 192 - (:unkn) unknown (My University, 1831)
Ch. 26, § 58: Prohibited the concealed carry of a dirk, pistol, sword-cane, or other dangerous weapon. Violators fined not exceeding one hundred dollars.
Keywords: CARRY - CONCEALED